Cellphones and whistles: Exploring the communicative ecology and sociality of the Enkanini informal settlement in Makhanda - Baloyi, Karabo (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
This thesis explores the communicative ecology in the Enkanini informal settlement in Makhanda, and in particular their use of mobile phones and whistles to build a sense of community. It makes the case for word-of-mouth as an integral part of the communicative ecology despite not being a technological device. It then examines the sociality that arises from the use of these devices, and how coloniality impacts on the participants' everyday experiences. The research was conducted through telephonic in-depth interviews with participants. To corroborate some of the content drawn from interviews, I used Grocott's Mail, Makhanda's only independent newspaper as an archival source, as well as some of the participants' Facebook profiles. This research argues that as a consequence of coloniality, Enkanini's residents suffer socio-economic challenges, and thus are unable to use digital technologies as much as they might like to, to communicate with their neighbours. As a consequence, word-of-mouth is their main form of communication with one another. Whistles are the 'low-tech' device used for community-wide communication to alert residents of an emergency, or about a meeting or protest. My findings contest generalised claims of society moving towards a network sociality, where individuality and project-based communication is valued over more communal forms of living. They also demonstrate the ways in which coloniality shapes almost every aspect of marginalised people's lives, making word of mouth the most significant form of communication, notwithstanding the apparent availability of digital technology. It also shows how a marginalised group uses the resources it has to pressure local government officials to provide them with the basis infrastructure they need for survival.
Keywords: Communication models; Cell phones Social aspects -- South Africa -- Makhanda; Cell phones Economic aspects -- South Africa -- Makhanda; Squatter settlements -- South Africa -- Makhanda; South Africa Social conditions 1994-; South Africa Economic conditions 1991-; South Africa Social life and customs; Communication Economic aspects -- South Africa -- Makhanda; Whistles -- South Africa -- Makhanda; Decolonization -- South Africa -- Makhanda; Communicative ecology